Compatibility of quantitative X-ray spectroscopy with continuous distribution models of water at ambient conditions - Johannes Niskanen; Mattis Fondell; Christoph J. Sahle; Sebastian Eckert; Raphael M. Jay; Keith Gilmore; Annette Pietzsch; Marcus Dantz; Xingye Lu; Daniel E. McNally; Thorsten Schmitt; Vinicius Vaz da Cruz; et al. (NATL ACAD SCIENCES, 2022)
The phase diagram of water harbors controversial views on underlying structural properties of its constituting molecular moieties, its fluctuating hydrogen-bonding network, as well as pair-correlation functions. In this work, long energy-range detection of the X-ray absorption allows us to unambiguously calibrate the spectra for water gas, liquid, and ice by the experimental atomic ionization cross-section. In liquid water, we extract the mean value of 1.74 +/- 2.1% donated and accepted hydrogen bonds per molecule, pointing to a continuous-distribution model. In addition, resonant inelastic X-ray scattering with unprecedented energy resolution also supports continuous distribution of molecular neighborhoods within liquid water, as do X-ray emission spectra once the femtosecond scattering duration and proton dynamics in resonant X-ray-matter interaction are taken into account. Thus, X-ray spectra of liquid water in ambient conditions can be understood without a two-structure model, whereas the occurrence of nanoscale-length correlations within the continuous distribution remains open.